Acute effects of high-intensity endurance exercise on subsequent resistance activity - Leveritt, M.; Abernethy, P. J. (The Journal of Strength and Conditioning Research, 1999)
This study investigated the effect of high-intensity endurance on subsequent isoinertial and isokinetic resistance exercise. One woman and five men (mean ± SD: age = 20.3 ± 2.5 years; body mass = 75.1 ± 10.2 kg; height = 177.8 ± 10.3 cm) performed isoinertial and isokinetic resistance exercise under control conditions (no experimental intervention) and after an acute bout of high-intensity endurance exercise. Endurance exercise consisted of five 5-minute bouts of incremental cycle exercise at between 40 and 100% of peak cycle ergometer oxygen consumption (peak o2). Isoinertial resistance exercise consisted of three sets of squats with a load of 80% of one repetition maximum. Isokinetic resistance exercise consisted of five repetitions of leg extensions performed at five different contractile speeds (1.05, 2.09, 3.14, 4.19, and 5.24 rad·s1). Significant reductions in isokinetic torque at 0.52 rad from full extension (T30) were observed after high-intensity endurance exercise. Endurance exercise also caused significant reductions in the number of isoinertial squat lifts performed. Plasma lactate values, measured before subjects performed resistance activity, were significantly higher after high intensity endurance exercise (6.16 ± 2.28 mmol·L1) when compared with the control condition (0.50 ± 0.45 mmol·L1). It was concluded that an acute bout of high-intensity endurance exercise may inhibit performance in a subsequent bout of resistance activity.